Aerosol Jet Printing as a Versatile Sample Preparation Method for Operando Electrochemical TEM Microdevices. Issue 20 (17th June 2022) - Morzy, Jędrzej K.; Sartor, Aileen; Dose, Wesley M.; Ou, Canlin; Kar‐Narayan, Sohini; De Volder, Michael F. L.; Ducati, Caterina
Abstract: Operando electrochemical transmission electron microscopy (ec‐TEM) is a promising tool for advanced characterization of energy systems close to their operating conditions. However, reliable sample preparation for the technique is particularly challenging due to spatial constraints. Here, a novel approach of manufacturing such samples is introduced and demonstrated for industrially relevant battery powders: NMC811 and LTO (LiNi0.8 Mn0.1 Co0.1 O2 and Li4 Ti5 O12 ). Aerosol‐jet printing is used to deposit microscale patterns of battery active material particles on the electrodes of commercial ec‐TEM chips. This method provides high spatial resolution (line width < 30 µm) and accuracy, ease of ink preparation, flexibility of materials, and ability to manufacture complex structures (layered or mixed materials). Size selectivity of aerosol jet printing and its positive implications for ec‐TEM sample preparation are also discussed. This procedure is a promising solution to the difficult problem of micro‐battery fabrication for ec‐TEM and for other applications where high spatial resolution deposition from powders is required. Abstract : A novel method for operando electrochemical transmission electron microscopy (TEM) microdevice fabrication is demonstrated. Using aerosol jet printing, fine features (line width <30 µm) can be printed in arbitrary shapes using a variety of industrially relevant materials. Here, this approach is used to create NMC811‐LTO microbatteries on commercially available operando TEM chips.